3317 Translating simulation-based team leadership training into patient-centered outcomes. (27th March 2019) - Fernandez, Rosemarie; Rosenman, Elizabeth D.; Chipman, Anne K.; Brolliar, Sarah; Vrablik, Marie C.; Misisco, Anthony T; Olenick, Jeff; Grand, James; Kalynych, Colleen; J. Kozlowski, Steve W.; Chao, Georgia T.
Abstract : OBJECTIVES/SPECIFIC AIMS: The objective of this research was to assess the clinical impact of simulation-based team leadership training on team leadership effectiveness and patient care during actual trauma resuscitations. This translational work addresses an important gap in simulation research and medical education research. METHODS/STUDY POPULATION: Eligible trauma team leaders were randomized to the intervention (4-hour simulation-based leadership training) or control (standard training) condition. Subject-led actual trauma patient resuscitations were video recorded and coded for leadership behaviors (primary outcome) and patient care (secondary outcome) using novel leadership and trauma patient care metrics. Patient outcomes for trauma resuscitations were obtained through the Harborview Medical Center Trauma Registry and analyzed descriptively. A one-way ANCOVA analysis was conducted to test the effectiveness of our training intervention versus a control group for each outcome (leadership effectiveness and patient care) while accounting for pre-training performance, injury severity score, postgraduate training year, and days since training occurred. Association between leadership effectiveness and patient care was evaluated using random coefficient modeling. RESULTS/ANTICIPATED RESULTS: Sixty team leaders, 30 in each condition, completed the study. There was a significant difference in post-training leadership effectiveness [F(1, 54)=30.19, p<.001, η2=.36] between the experimental and control conditions. There was no direct impact of training on patient care [F(1, 54)=1.0, p=0.33, η2=.02]; however, leadership effectiveness mediated an indirect effect of training on patient care. Across all trauma resuscitations team leader effectiveness correlated with patient care (p<0.05) as predicted by team leadership conceptual models. DISCUSSION/SIGNIFICANCE OF IMPACT: This work represents a critical step in advancing translational simulation-based research (TSR). While there are several examples of high quality translational research programs, they primarily focus on procedural tasks and do not evaluate highly complex skills such as leadership. Complex skills present significant measurement challenges because individuals and processes are interrelated, with multiple components and emergent nature of tasks and related behaviors. We provide evidence that simulation-based training of a complex skill (team leadership behavior) transfers to a complex clinical setting (emergency department) with highly variable clinical tasks (trauma resuscitations). Our novel team leadership training significantly improved overall leadership performance and partially mediated the positive effect between leadership and patient care. This represents the first rigorous, randomized, controlled trial of a leadership or teamwork-focused training that systematically evaluates the impact on process (leadership) and performance (patient care).